AstraZeneca Vaccine Administration and Treatment Outcomes in Cardiovascular Patients - Chastity, Phoebe Clarissa; Ramatillah, Diana Laila (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Cardiovascular disease (CVD) is a leading cause of morbidity and mortality worldwide. With the global rollout of COVID-19 vaccines, including the AstraZeneca vaccine, there is increasing interest in understanding their impact on individuals with pre-existing cardiovascular conditions. While effective in preventing COVID-19, concerns have been raised about potential cardiovascular side effects. This study aimed to determine the correlation between the AstraZeneca vaccine and treatment outcomes in CVD patients, focusing on differences in patients' CVD-related conditions before and after vaccination. Data were collected using validated questionnaires conducted in Jakarta, employing an analytical survey with a cohort approach. Reliability was assessed using Cronbach's alpha, and validity was tested with a modified Delphi method involving clinical pharmacy experts. Data were analyzed using crosstab analysis via Chi-square test. The study included 200 subjects, with 115 females (57,5%) and 85 males (42,5%), with a majority of participants being over 45 years old (45,0%). A significant correlation (p-value < 0,05) was observed across various factors, including comorbidities and sociodemographic variables, patients' drug intake before and after vaccination, and the relationship between vaccination and comorbid diseases. The findings indicate a strong association between vaccination and patients history of cardiovascular disease. This correlation highlights the vaccine's possible impact on CVD-related symptoms post-vaccination. Consequently, the research provides evidence that the AstraZeneca vaccination significantly affects the risk of cardiovascular disease.